Reestructuración técnico administrativa en la empresa Inprelco S.A.S. (2017)
The technical and administrative restructuring of the company Inprelco S.A.S was made through four chapters, in the diagnosis, were used tools like the Chamber of commerce Self-testing for determinate the internal organization´s overview, a PESTEL analysis was developed even Latin America, Colombia and Bogota, to analyze external factors, supplementary was used SWOT matrix, in this are proposed improvement strategies for the organization. Subsequently was made the technical research, that was based in the Strategy of Business Unit corresponding to Electrical Construction and assembly Substations, in this was proposed Unit Prices Analyze for the principal assemblies that constitute the operation, in order to a correct materials, equipment and tools control, was done execute project procedure too, also was made the development to supplier and provision management. Later, was done administrative research, in this is recommended to do regular trainings to organization´s partners, the strategic planning improvement and the creation of the human talent area too, was suggested wage research and its respective improvement.